Evaluasi Keanggotaan Indonesia dalam Port State Measure Agreement (PSMA) 2009 dalam Menghadapi IUU Fishing (Evaluasi Keanggotaan Indonesia dalam Port State Measure Agreement (PSMA) 2009 dalam Menghadapi IUU Fishing) - Arie Afriansyah; Gurnita Ning Kusumawati (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2021)
Protection of the utilization of marine resources and improvement of the Indonesian maritime and fishery economy isconducted by preventing Illegal, Unreported, and Unregulated Fishing (IUU Fishing) in the fishing ground zone. This isembodied in various international instruments, one of which is the 2009 Agreement on Port State Measures to Prevent,Deter, Eliminate IUU Fishing (PSMA 2009). The availability of human resources and technology in preparing facilities andlaw enforcement in the marine area of the economic zone is one of the challenges for Indonesia in realizing the internationalPSMA 2009 instrument. The focus of the discussion in this paper are: first, Indonesia’s efforts to maximize PSMA 2009by conducting research, especially with regard to the problem of unregulated fishing at the Ocean Port of Nizam Zachman.Second, the importance of reformulation of Indonesia’s positive law regarding PSMA to tackle IUU fishing activities. Thisstudy uses a normative juridical research method with a statute approach and a comparative approach. Indonesia’s effortsin implementing the 2009 PSMA consistently and sustainably, as was done at the Nizam Zachman Ocean Fishing Port,Jakarta, are assessed from several indicators such as fishing port facilitation, law enforcement, and human resources beforeand after the implementation of the 2009 PSMA. However, there is still a need for policy reformulation in terms of lawenforcement and strategies for optimizing infrastructure at Indonesian fishing ports. AbstrakProtection of the utilization of marine resources and improvement of the Indonesian maritime and fishery economy isconducted by preventing Illegal, Unreported, and Unregulated Fishing (IUU Fishing) in the fishing ground zone. This isembodied in various international instruments, one of which is the 2009 Agreement on Port State Measures to Prevent,Deter, Eliminate IUU Fishing (PSMA 2009). The availability of human resources and technology in preparing facilities andlaw enforcement in the marine area of the economic zone is one of the challenges for Indonesia in realizing the internationalPSMA 2009 instrument. The focus of the discussion in this paper are: first, Indonesia’s efforts to maximize PSMA 2009by conducting research, especially with regard to the problem of unregulated fishing at the Ocean Port of Nizam Zachman.Second, the importance of reformulation of Indonesia’s positive law regarding PSMA to tackle IUU fishing activities. Thisstudy uses a normative juridical research method with a statute approach and a comparative approach. Indonesia’s effortsin implementing the 2009 PSMA consistently and sustainably, as was done at the Nizam Zachman Ocean Fishing Port,Jakarta, are assessed from several indicators such as fishing port facilitation, law enforcement, and human resources beforeand after the implementation of the 2009 PSMA. However, there is still a need for policy reformulation in terms of lawenforcement and strategies for optimizing infrastructure at Indonesian fishing ports.